Evolving genres a critical examination of genre analysis from 1995 to 2023 - Zhou Lijie; Sabariah Abd Rahim; Daron Benjamin Loo (Pusat Penataran Ilmu dan Bahasa,Universiti Malaysia Sabah, 2024)
This article focuses on conducting genre analysis on research articles obtained from the core collection of the Web of Science database, specifically covering the period from 1995 to 2023. The study employs advanced scientific tools, notably CiteSpace, to analyse the keyword hot spot in the field of genre analyis. These statistics methodically examine the intrinsic correlation and evolution of the research issue in genre analysis. This paper utilises bibliometrics and scientific knowledge mapping. The following results were acquired by a thorough investigation of the numerical data: Keyword hot spot analysis tracks the changes in genre analysis, showing funtional change, contextual change, and critical trend. According to the data, the researchers claim that genre analysis has evolved within the Web of Science Core Collection. The present study is of great importance as it offers crucial insights to researchers in the field of genre Analysis.